African swine fever virus infection activates inflammatory responses through downregulation of the anti-inflammatory molecule C1QTNF3 - Lv, Changjie; Zhang, Qiang; Zhao, Li; Yang, Jingyu; Zou, Zhong; Zhao, Ya; Li, Chengfei; Sun, Xiaomei; Lin, Xian; Jin, Meilin (Frontiers in Immunology, 2022)
African swine fever (ASF) is the most dangerous pig disease, and causes enormous economic losses in the global pig industry. However, the mechanisms of ASF virus (ASFV) infection remains largely unclear. Hence, this study investigated the host response mechanisms to ASFV infection. We analyzed the differentially expressed proteins (DEPs) between serum samples from ASFV-infected and uninfected pigs using quantitative proteomics. Setting the p-value < 0.05 and |log2 (fold change)| > 1.5, we identified 173 DEPs, comprising 57 upregulated and 116 downregulated proteins, which belonged to various biological processes and pathways based on the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses. The enriched pathways include immune responses, metabolism, and inflammation signaling pathways. Western blot analysis validated the DEPs identified using quantitative proteomics. Furthermore, our proteomics data showed that C1QTNF3 regulated the inflammatory signaling pathway. C1QTNF3 knockdown led to the upregulation of pro-inflammatory factors IL-1β, IL-8, and IL-6, thus inhibiting ASFV replication. These results indicated that C1QTNF3 was critical for ASFV infection. In conclusion, this study revealed the molecular mechanisms underlying the host-ASFV interaction, which may contribute to the development of novel antiviral strategies against ASFV infection in the future.